Dynamic alterations of metabolites revealed the vascularization progression of bioengineered liver. Issue 10 (29th July 2022) - Zhou, Qian; Guo, Beibei; Chen, Deying; Yao, Heng; Liang, Xi; Xin, Jiaojiao; Shi, Dongyan; Ren, Keke; Yang, Hui; Jiang, Jing; Li, Jun
Abstract: Vascularization is a critical but challenging process in developing functional bioengineered livers with the decellularized liver scaffolds (DLSs) and the process is accompanied by cell‐specific metabolic alterations. To elucidate the dynamic alterations of metabolites during vascularization, rat DLSs were vascularized with human umbilical vein endothelial cells and liquid chromatography mass spectrometry‐based metabolomics was performed on culture supernatants collected at 0, 1, 3, 7, 14, and 21 days. Overall, 1698 peak pairs or metabolites were detected in the culture supernatants, with 309 metabolites being positively identified. The orthogonal partial least‐squares discriminant analysis and functional enrichment analysis revealed three phases that could be clearly discriminated, including Phase D1 (cell proliferation and migration), Phase D3D7 (vascular lumen formation), and Phase D14D21 (functional endothelial barrier formation). Seventy‐two common differentially abundant metabolites of known identity were detected in these three phases when compared with Day 0. Of these metabolites, a high level of β‐Alanine indicated a better degree of vascularization and 14 days of in vitro dynamic culture is required to develop a functionalized vascular structure. These results enriched our understanding of the metabolic mechanism of DLS vascularization and indicated that β‐Alanine could function as a potential predictor of the patency of vascularized bioengineered livers. Abstract : The dynamic alterations of metabolites during the vascularization process in developing functional bioengineered livers with the decellularized liver scaffolds (DLSs) are described. Here, Li et al. have vascularized the DLSs with human umbilical vein endothelial cells and revealed three phases of the vascularization process via liquid chromatography mass spectrometry‐based metabolomics, among which a high level of β‐Alanine on Day 14 was identified to predict the patency of vascularized bioengineered livers, which confirmed our previous finding that 14 days of in vitro dynamic culture is required for DLS vascularization.